National study of utilization of male incontinence procedures. Issue 1 (18th October 2014) - Chughtai, Bilal; Sedrakyan, Art; Isaacs, Abby J.; Mao, Jialin; Lee, Richard; Te, Alexis; Kaplan, Steven
Abstract: Aims: We explored re‐interventions and short and long term adverse events associated with procedures for male incontinence among Medicare beneficiaries. Methods: All inpatient and outpatient claims for a simple random sample of Medicare beneficiaries for 2000–2011 were queried to identify patients of interest. All male patients with an International Classification of Diseases, 9th Edition (ICD‐9) diagnosis code for stress incontinence or mixed incontinence were included. Artificial urinary sphincter recipients, patients who underwent a sling operation and those receiving an injection of a bulking agent were identified with Current Procedure Terminology (CPT‐4) and ICD‐9 Procedure Codes. Results: The entire cohort of 1, 246 patients were operated on between 2001 and 2011. 34.9% of them received an artificial urinary sphincter (AUS), 28.7% with a bulking agent, and 36.4% with a sling. There were no statistically significant differences in demographics or comorbidities between the treatment groups, except that more sling patients were obese ( P  = 0.006) and fewer bulk patients had diabetes ( P  = 0.007). There are, however, significant changes in procedures selected over time ( P  < 0.001). In the first year and over the entire follow‐up after surgery, patients treated with bulking agents had the most subsequent interventions (40.1% and 52.9%), followed by sling (10.4% and 15.5%), and AUS (2.3% and 20%) ( P  < 0.001). Post‐operative and 90 day complications were low. Conclusions: All three treatments seem to be safe among Medicare beneficiaries with multiple comorbidities. The urological, infectious, and neurological complication occurrences were low. Neurourol. Urodynam. 35:74–80, 2016 . © 2014 Wiley Periodicals, Inc.